2020
DOI: 10.1016/j.psj.2020.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with canthaxanthin and 25-hydroxycholecalciferol has beneficial effects on bone and oxidative metabolism in European quail breeders

Abstract: This study aimed to investigate the effect of supplementation with canthaxanthin ( Cx ) and 25-hydroxycholecalciferol ( 25-OH-D 3 ) on the production performance, egg quality, bone mineral content, blood biochemical parameters, and antioxidant status of European quail breeders. Two hundred and forty quail breeders were distributed in a completely randomized design with 5 diets and 8 replicates of 4 females and 2 males were used. All quail breeders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
(39 reference statements)
2
7
0
Order By: Relevance
“…However, concerning with the main effect of vitamin D3 effects, no significant difference due to vitamin D3 on FCR during the whole experiment. These results are consistent with Bonagurio et al (2020) who reported that supplementation of (25-OH-D3 did not influence FCR. Fatahi et al (2019) reported that the feed conversion ratio in 4000 IU/kg of vitamin D3 (3.…”
Section: Feed Conversion Ratio (Fcr)supporting
confidence: 93%
See 1 more Smart Citation
“…However, concerning with the main effect of vitamin D3 effects, no significant difference due to vitamin D3 on FCR during the whole experiment. These results are consistent with Bonagurio et al (2020) who reported that supplementation of (25-OH-D3 did not influence FCR. Fatahi et al (2019) reported that the feed conversion ratio in 4000 IU/kg of vitamin D3 (3.…”
Section: Feed Conversion Ratio (Fcr)supporting
confidence: 93%
“…The results of vitamin D3 supplementation indicated that, there were no significant differences in feed consumption when adding vitamin D3 with all levels during the experiment periods. The obtained results agreed with Bonagurio et al (2020) who reported that supplementation of (25-OH-D3 did not influence FC. Also, Adhikari et al (2020) showed that there was no difference in FC between hens fed diets supplemented with different levels of vitamin D3 and 25-OHD.…”
Section: Feed Consumption (Fc)supporting
confidence: 91%
“…An inadequate amount of Ca and vitamin D supplementation during the initial phase may cause an imbalance in mineral homeostasis, inappropriate bone development and abnormal calcification. Bonagurio et al (2020), evaluated that die-tary supplementation with canthaxanthin and 25-hydroxycholecalciferol has beneficial effects on bone (femoral and tibiotarsal dry weight and calcium content) in European quail breeders, but production performance was not influenced by diet. Sheikhlar & Navid (2009), evaluated four different levels of 1,25-Dihydroxycolecalciferol supplementation (from 2.5 to 8.5 ug/kg 1,25 (OH) 2 D3) in diets containing 0.71% Ca and 0.37% total phosphorus in quails between 0 to 3 weeks of age; they did not observe an effect of vitamin D supplementation on WG or FC.…”
Section: Discussionmentioning
confidence: 99%
“…Canthaxanthin ( Cx ) combined with 25-hydroxycholecalciferol ( 25-OH-D 3 ) is a commercial additive commom applied in diets of poultry. Supplementation of breeder diets with synthetic carotenoids, such as Cx, successfully increase the concentration of antioxidant compounds and, consequently, reduces the formation of reactive oxygen species ( Surai et al, 2016 ), in the oviduct trait ( Bonagurio et al, 2020 ), plasma and serum ( Karadas et al, 2016 ), and cell membranes ( Mathimaran et al, 2021 ). Although, the Cx supplementation inhibits polyunsaturated fatty acids ( PUFAs ) peroxidation in sperm cell membranes, increasing sperm cell survival and flock fertility ( Rosa et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…This vitamin D metabolite has a high absorption rate and increases the efficiency of calcium absorption in the intestine. As a consequence of an increased circulating calcium levels, breeders produce eggs with a thicker shell ( Bonagurio et al, 2020 ), minimizing the risk of breakage and contamination of the egg with infectious agents ( Bar et al, 1980 ).…”
Section: Introductionmentioning
confidence: 99%